A Study Of The Relationship Between Sectoral Bank Credit And Financial Performance During The Period 2011-2018 ( Applied Study on Bemo Saudi Fransi Bank) - عبد الهادي الرفاعي; سارة الخير (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to identify the banking facilities in Bemo Bank and what is the strategy to diversify its methods according to the economic sector, and to discover the relationship between banking facilities according to the economic sector and the financial performance of Bemo Saudi Fransi Bank. The research relied on following the descriptive analytical approach to show that banks follow the strategy of diversifying banking facilities and their relationship to financial performance, and was represented by an applied study on Bemo Saudi Fransi Bank, being one of the leading banks in Syria and the stability of its time series. Among the most important results, there is a significant relationship between credit by sector and the financial performance indicators of Bemo Saudi Fransi bank, which is expressed in a legal compound pair, which is very strong 0.999. The agriculture and services sector, coupled with a decrease in the capital adequacy ratio and an increase in the default rate, the return on assets, and the ratio of facilities to deposits One of the most important recommendations is to work on restoring the activity of grants to the economic sectors, especially the industrial ones, and to work to raise their contribution better than before, due to the urgent need to raise the production and industrial capacity and expand the volume of community services, due to what the country faced during the war.